(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
In this article, the pedagogical possibilities of developing the musical spirituality of students are highlighted from a certain point of view, and the first spiritual and musical concepts, that is, the first musical concepts of the students, are necessarily first brought to preschool educational institutions. they were given knowledge through ongoing musical training. Gradually, as the child grows up, a person’s world view and feelings develop. Based on the life experiences of the students from the school period, a certain feeling of the spiritual worldviews and thoughts of the worldviews unique to them begin to appear in the basis of each music.